China [videorecording] beyond the clouds - Agland, Phil; Noxon, Nick; Simon, Tom (The Society, 1994)
Documents Lijiang, market town in Southwest China and the Chinese community - how they face economic reform, gang violence and drug abuse. Includes the way of life of the Lu family, Mr. Mu's dealing with the aftermath of his nephew's murder and the Chinese officers inquiry into the teenager's death and Dr. Tang's acupuncture treatment.